Advances on separation diastereomers of acyclic isoprenoid alkanes by gas chromatography and its geochemical significance. (1st February 2019) - Wu, Yingqin; Liu, Yanhong; Wang, Yongli; Xia, Yanqing; Wang, Youxiao
Abstract: The abundant acyclic isoprene alkanes, including norpristane (2, 6, 10-tetramethyltetradecane), pristane (2, 6, 10, 14-tetramethylpentadecane), phytane (2, 6, 10, 14-tetramethylhexadecane) and their diastereomers, were detected and separated by GC-MS/MS in the coal sample of the Junggar Basin. Furthermore, the optimized condition of separation were discussed in terms of column type, length, and column temperature program. The results showed that the separation degree (R) of their diastereomers (i.e., 6(R)10(S)), 6(S)10(S) + 6(R)10(R)) of norpristane, pristane and phytane reached 0.6, 0.8 and 0.9, respectively. It indicated that the method was versatile, simple, rapid and efficient to separate the diastereomers of acyclic isoprene alkanes.